Autoethnographies of Border-Crossing and In-Betweenness of International Doctoral Students' Voices in the United States - Herrera, Luis Javier Pentón; Trịnh, Ethan; Yazan, Bedrettin (Educational Research E-Books Online, Collection 2025., 2025)
This edited volume powerfully captures autoethnographies of international doctoral students in the U.S. and unravels a plethora of their experiences that oscillate between challenges and triumphs of navigating in-betweenness in their unique journeys. The concepts of border-crossing and in-betweenness encapsulate more than just a mere geographic displacement. Rather, they delineate the intricate dance of cultural, emotional, intellectual, and oftentimes, spiritual, transitions, often fraught with tension and self-reflection. As such, 12 chapters in this book will provide the readers with invaluable insights and foster a deeper empathy and understanding of the complexities faced by international students in the U.S. Contributors are: Saurabh Anand, Nadia Bhuiyan, Miriam Furlan Brighente, Heewon Chang, Suparna Chatterjee, Hanh Dinh, Sumeyra Gok, Monisha Issano Jackson, Grace Jue Yeon Kim, Nasiba Norova, Luis Javier Pentón Herrera, Lakmini Grant Siriwardana, Natalie Thibault, Ethan Trinh, Ngoc Tung Vu, Abir Ward, Zhenjie Weng, Bedrettin Yazan, Eun Young Yeom, Jing Yu and Jingyi Zhu.